2019
DOI: 10.3390/pathogens8040242
|View full text |Cite
|
Sign up to set email alerts
|

Com1 as a Promising Protein for the Differential Diagnosis of the Two Forms of Q Fever

Abstract: Coxiella burnetii is the causative agent of acute and chronic Q fever in humans. Although the isolates studied so far showed a difference in virulence potential between those causing the two forms of the disease, implying a difference in their proteomic profile, the methods used so far to diagnose the two forms of the disease do not provide sufficient discriminatory capability, and human infections may be often misdiagnosed. The aim of the current study was to identify the outer membrane Com1 (CBU_1910) as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…While commercial ELISAs use whole cell lysates offering a broad variety of antigens, the here developed recombinant ELISA is based on a single, well-defined antigen. However, the vast majority of Q fever true positive animals (83% in total) reacted to recombinant Com1 protein indicating its diagnostic value as already shown for mice and just recently for humans [ 48 , 55 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…While commercial ELISAs use whole cell lysates offering a broad variety of antigens, the here developed recombinant ELISA is based on a single, well-defined antigen. However, the vast majority of Q fever true positive animals (83% in total) reacted to recombinant Com1 protein indicating its diagnostic value as already shown for mice and just recently for humans [ 48 , 55 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 80%
“…Com1 as a chaperon catalyzes the formation of disulfide bonds in extra cytoplasmic proteins [ 52 , 53 ]. It has recently repeatedly been shown that Com1 as an antigen in an ELISA with human sera can lead to acceptable performance of the test with specificities of about 90% [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, CBU_1910 (Com1) has been described in the literature as a credible diagnostic marker, exposed on the surface of C. burnetii. Furthermore, this protein has been perfectly described by Vranakis et al (2019), as a very good marker for the differential diagnosis of the chronic form of Q fever. More specifically, an ELISA assay was used in their study in order to screen blood sera from patients suffering either from the chronic or the acute phase of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…The results of the current work together with our results of the Com1 (Vranakis et al, 2019) may be considered as a first step for the production of a serodiagnostic test that will be able to correctly diagnose chronic Q fever.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation